Effect of vegetation cover and sediment type on 3D subsurface structure and shear strength in saltmarshes. Issue 11 (29th June 2021) - Chirol, Clementine; Spencer, Kate L.; Carr, Simon J.; Möller, Iris; Evans, Ben; Lynch, Jason; Brooks, Helen; Royse, Katherine R.
Abstract: The vulnerability of saltmarshes to lateral erosion at their margin depends on the local biogeomorphological properties of the substrate. In particular, the 3D architecture of pore and root systems is expected to influence shear strength, with repercussions for the wider‐scale stability of saltmarshes. We apply X‐ray computed microtomography (μCT) to visualize and quantify subsurface structures in two UK saltmarshes at Tillingham Farm, Essex (silt/clay rich substrate) and Warton Sands (sand‐rich substrate), with four types of ground cover: bare ground, Spartina spp, Salicornia spp and Puccinellia spp . We extracted μCT structural parameters that characterize pore and root morphologies at each station, and compared them with field measurements of shear strength using a principal component analysis and correlation tests. The 3D volumes show that species‐dependent variations in root structures, plant colonization events and bioturbation activity control the morphology of macropores, while sediment cohesivity determines the structural stability and persistence of these pore structures over time, even after the vegetation has died. Areas of high porosity and high mean pore thickness were correlated to lower values of shear strength, especially at Tillingham Farm, where well‐connected vertical systems of macropores were associated with current or previous colonization by Spartina spp . However, while well‐connected systems of macropores may lower the local deformation threshold of the sediment, they also encourage drainage, promote vegetation growth and reduce the marsh vulnerability to hydrodynamic forces. The highest values of shear strength at both sites were found under Puccinellia spp, and were associated with a high density of mesh‐like root structures that bind the sediment and resist deformation. Future studies of marsh stability should ideally consider time series of vegetation cover, especially in silt/clay‐dominated saltmarshes, in order to consider the potential effect of preserved buried networks of macropores on water circulation, marsh functioning and cliff‐face erosion. Abstract : We use µCT to analyse 3D substrate structures in two UK saltmarshes (sand‐rich and clay‐rich) under different vegetation covers, and infer links between porosity, root architecture and shear strength. Spartina spp and Puccinellia spp have contrasting root architectures (tap root and fibrous respectively), with higher shear strength values found under Puccinellia spp . Well‐preserved and highly connected vertical systems of macropores at the muddy site lower the internal shear strength of the substrate but promote drainage, vegetation growth and marsh stability.